Why government supported smart city initiatives fail: Examining community risk and benefit agreements as a missing link to accountability for equity-seeking groups - Sengupta, Ushnish; Sengupta, Ulysses (Frontiers in Sustainable Cities, 2022)
This paper utilizes concepts from a critical social justice discourse on smart cities to identify factors behind resistance to new smart city initiatives from equity seeking groups. The broader critical discourse is examined based on relevance to the eventual failure of the initiatives selected as case studies. It highlights institutional failure within government supported initiatives due to the lack of consideration given to equitable distribution of risks and formal accountability mechanisms. It describes outcomes surrounding smart cities in which the benefits accrue to some groups within the city while risks increase for other groups. Finally, we examine the integration of ‘risk’ as an adaptation to the existing practical mechanism of Community Benefit Agreements, for use of this framework to support value sensitive design approaches in future smart city initiatives.